2023
DOI: 10.20944/preprints202304.0807.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Countering and Tackling Advanced First-Line Immune Evasion Represents the Most Feasible and Precise Approach to Control and Eradicate Rabies

Abstract: Despite being a rare disease worldwide, rabies has the highest morbidity and mortality rates, with roughly 99% of symptomatic cases leading to coma and death. Rabies represents an infectious disease caused by the Rabies virus (RABV), which is part of the Lyssavirus group and the Rhabdoviridae family, and it mainly spreads through the bite and scratch of an infected mammal, but particularly of wild animals, such as bats, foxes, wolves and racoons, and of domestic animals, such as dogs and cats, in rabies-prone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…As a result of a potentially increased trained immunity of T-lymphocytes, they may slowly undergo a process of transformation into "super-lymphocytes", whilst not denying the fact that a number of host T-lymphocytes will still undergo apoptosis following infection with HIV. In short, a thorough understanding of the processes of human and microbial evolution would require adjustment through the apprehension of the fact that physics represents the foundational layer of all Earthly sciences, which means that biological phenomena are in fact dependent upon the theories, principles and laws observed in physics (Carp T., 2023). Perhaps through a similar kind of research pattern, scientific data collected from various clinical trials showed not only that the innate immune system contains its own "memory", but that it contains "specific memory" (Kurtz J., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of a potentially increased trained immunity of T-lymphocytes, they may slowly undergo a process of transformation into "super-lymphocytes", whilst not denying the fact that a number of host T-lymphocytes will still undergo apoptosis following infection with HIV. In short, a thorough understanding of the processes of human and microbial evolution would require adjustment through the apprehension of the fact that physics represents the foundational layer of all Earthly sciences, which means that biological phenomena are in fact dependent upon the theories, principles and laws observed in physics (Carp T., 2023). Perhaps through a similar kind of research pattern, scientific data collected from various clinical trials showed not only that the innate immune system contains its own "memory", but that it contains "specific memory" (Kurtz J., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of a potentially increased trained immunity of T-lymphocytes, they may slowly undergo a process of transformation into "super-lymphocytes", whilst not denying the fact that a number of host T-lymphocytes will still undergo apoptosis following infection with HIV. In short, a thorough understanding of the processes of human and microbial evolution would require adjustment through the apprehension of the fact that physics represents the foundational layer of all Earthly sciences, which means that biological phenomena are in fact dependent upon the theories, principles and laws observed in physics (Carp T., 2023). Perhaps through a similar kind of research pattern, scientific data collected from various clinical trials showed not only that the innate immune system contains its own "memory", but that it contains "specific memory" (Kurtz J., 2005).…”
Section: Discussionmentioning
confidence: 99%